Scoping Review: Hubungan Sanitasi Lingkungan dengan Kejadian Skabies pada Santri di Pondok Pesantren - Imam Syukur Saraha; Ismawati; Sara Puspita (Bandung Conference Series: Medical Science, 2022)
Abstract. Scabies is a skin disease caused by infection with Sarcoptes scabiei var Hominis, occurring with a prevalence of about 200 million people each year due to the low economy, inadequate levels of environmental hygiene and sanitation. Scabies is mostly found in densely populated areas such as dormitories, Islamic boarding schools, hospitals, prisons and nursing homes. Environmental sanitation is one of the factors that can affect the transmission of scabies whose variables consist of ventilation, humidity, lighting, temperature, availability of clean water and residential density. The purpose of this study was to determine the relationship between environmental sanitation and the incidence of scabies in students in Islamic boarding schools. The research uses a scoping review study through the Google Schoolar, ProQuest, Science Direct, and Garuda Portal databases with a feasibility test using the JBI Critical Appraisal Checklist. The total number of initial articles in this study was 289 articles, while the number of articles that met the eligibility criteria was 7 articles. The results showed that 6 out of 7 articles stated that there was a relationship between ventilation, clean water supply, occupancy density, lighting, temperature and humidity with the incidence of scabies. The conclusions of this study indicate that there is a relationship between environmental sanitation and the incidence of scabies in students at Islamic boarding schools. Abstrak. Skabies merupakan penyakit kulit yang diakibatkan oleh infeksi Sarcoptes scabiei var Hominis, terjadi dengan prevalensi sekitar 200 juta orang setiap tahunnya diakibatkan oleh ekonomi rendah, tingkat kebersihan dan sanitasi lingkungan yang tidak memadai. Skabies banyak terdapat pada wilayah yang padat penduduk seperti asrama, pesantren, rumah sakit, penjara dan panti jompo. Sanitasi lingkungan merupakan salah satu faktor yang dapat memengaruhi penularan skabies yang variabelnya yang terdiri dari ventilasi, kelembaban, pencahayaan, suhu, ketersediaan air bersih dan kepadatan hunian. Tujuan penelitian ini adalah untuk mengetahui hubungan sanitasi lingkungan dengan kejadian skabies pada santri di pondok pesantren. Penelitian menggunakan studi scoping review melalui database Google Schoolar, ProQuest, Science Direct, dan Portal Garuda dengan uji kelayakan menggunakan JBI Critical Appraisal Checklist. Total jumlah artikel awal pada penelitian ini sebanyak 289 artikel, sedangkan jumlah artikel yang memenuhi kriteria kelayakan sebanyak 7 artikel. Hasil penelitian menunjukkan sebanyak 6 dari 7 artikel menyatakan terdapat hubungan ventilasi, penyediaan air bersih, kepadatan hunian, pencahayaan, suhu dan kelembaban dengan kejadian skabies. Simpulan dari penelitian ini menunjukkan adanya hubungan sanitasi lingkungan dengan kejadian skabies pada santri di pondok pesantren.